Clostridium Histolyticum Collagenase Underdosed for Multicord Injection in Dupuytren's Disease: A Retrospective Cohort Study. Issue 11 (21st November 2022) - Boriani, Filippo; Raggini, Filippo; Evangelista, Andrea; Gustar, Adrian; Figus, Andrea
Abstract : Background: An underdosing of collagenase clostridium histolyticum (0.32 mg) is proposed as a potentially effective option in patients with additional cords in the same hand, after the first cord has been treated with the regular dose of 0.58 mg. The aim of this study was to analyze whether this additional dose is tolerated and effective. Methods: Patients with Dupuytren's disease affecting MCP joints with at least two independent pathological cords, causing deformity of two digits, were considered, with their written informed consent, for a simultaneous injection of the two cords with a single vial of collagenase. Digits treated with the standard dose of 0.58 mg were compared with digits injected with the smaller dose of 0.32 mg. Passive extension deficit and range of motion were evaluated after injection. Complications were also compared. Results: A total of 26 patients (29 hands) were included in the study. Of these, nine patients had two independent cords within one hand, and 17 patients had a single cord (three of these with a cord in each hand). Thirty-five digits were injected, 23 with 0.58 mg and 12 with 0.32 mg. Apart from a smaller mean percentage variation in passive extension deficit within 24 hours in the 0.58-mg dose compared with 0.32 mg (29% versus 40%, P = 0.031), no other differences emerged if a dose of 0.32 mg is used instead of 0.58 mg, in terms of selected outcome measures and rate of complications ( P > 0.05). Conclusion: Underdosing collagenase clostridium histolyticum is equally effective in the treatment of Dupuytren's disease.